Assessing of Science Literacy Skills of Natural Science Pre-Service Teachers Through Virtual Laboratory-Based Scientific Approach - Muh. Tawil; Bakkara, Hasanuddin; Putra, Andry S. Utama (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to assess the science literacy skills of science: 1) the activity of natural science pre-service teachers; 2) the improvement of science literacy skills of groups A and B; 3) whether there is a difference in the average score and the improvement of science literacy skills before and after learning in group A and B; 4) whether there is no difference in the average score of the n-gain of science literacy skills of group A and B; and 5) how big is the effect size of the science literacy skills of group A and B. Pre-experimental research method, the number of samples of each group A and B (n = 29) were determined by purposive sampling. Data analysis was descriptive and inferential. The research instrument, a science literacy test, consisted of 20 multiple-choice questions with a value range of 0-100, which were valid (Vc = 1) and reliable (100%). Prospective science teachers who participated in the virtual laboratory-based scientific approach demonstrated an average score increase of 48% in science literacy skills for group A and 46% for group B. There was a difference in the average score of science literacy before and after learning in both groups. However, there was no significant difference in the average n-gain score between the two. The effect size in group A was in the high category (1.0), while group B was in the medium category (0.4). These results indicate that the science literacy skills of prospective teachers still need to be improved through training that combines the scientific approach and virtual laboratory so that they can be directly involved in the development of science literacy.